2016
DOI: 10.1002/hed.24479
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose distribution in the teeth, maxilla, and mandible of patients with oropharyngeal and nasopharyngeal tumors who were treated with intensity‐modulated radiotherapy

Abstract: A dose distribution map was generated based on the estimated doses received, which could allow prediction of the areas most affected by radiation and facilitate further correlations with dental complications after radiotherapy. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1708-1716, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…These trends include a higher radiation dose for posterior teeth (molars followed by premolars) than for anterior teeth and greater radiation exposure of dental groups ipsilateral to the tumor than of dental groups contralateral to the tumor. 5,16,17,19,20 Tumor size was also found to be a predictive factor in our models for greater expected radiation dose, just as previous studies have found that larger tumors have greater radiation doses delivered to the anterior teeth and to the entire mandible (regardless of tumor laterality). 16,20 In our models, overall stage was a predictive variable for maximum radiation dose.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…These trends include a higher radiation dose for posterior teeth (molars followed by premolars) than for anterior teeth and greater radiation exposure of dental groups ipsilateral to the tumor than of dental groups contralateral to the tumor. 5,16,17,19,20 Tumor size was also found to be a predictive factor in our models for greater expected radiation dose, just as previous studies have found that larger tumors have greater radiation doses delivered to the anterior teeth and to the entire mandible (regardless of tumor laterality). 16,20 In our models, overall stage was a predictive variable for maximum radiation dose.…”
Section: Discussionsupporting
confidence: 71%
“…5,16,17,19,20 Tumor size was also found to be a predictive factor in our models for greater expected radiation dose, just as previous studies have found that larger tumors have greater radiation doses delivered to the anterior teeth and to the entire mandible (regardless of tumor laterality). 16,20 In our models, overall stage was a predictive variable for maximum radiation dose. Although an earlier study had not found a relationship between cervical nodal metastasis and mandibular radiation dose, it is possible that this conclusion was due in part to the small size of the sample group.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Parahyba el al. reported on the radiation dose distribution of nasopharyngeal patients treated with IMRT, and found that molar regions of the maxilla and mandible would most likely receive high doses of radiation due to its proximity to the nasopharynx . This would put the molar regions in these patients at the highest risk of developing ORN.…”
Section: Discussionmentioning
confidence: 99%